Photonic-assisted time-interleaved ADC based on optical delay line. (11th December 2015) - Xu, Chen; Zheng, Shilie; Chen, Xinyi; Chi, Hao; Jin, Xiaofeng; Zhang, Xianmin
Abstract: An approach to implement photonic-assisted time-interleaved analog-to-digital conversion and its calibration method are presented. The analog modulated optical signal is divided into M channels, suffering different time delay induced by optical delay lines which provide great flexibility in producing time intervals and is then sampled by electronic analog-to-digital converters (ADCs). The channel mismatches resulting in performance degradation are estimated by a modified sine wave fitting method. The time mismatch and other mismatches are corrected by fine optical delay adjustment and digital processing, respectively. A four-channel photonic-assisted time-interleaved analog-to-digital converter (TIADC) system operating at 40 GSa s −1 was demonstrated experimentally. The photonic-assisted TIADC system was tested with a 6.31 GHz sine wave signal, exhibiting 40.3 dB signal-to-noise and distortion ratio (SINAD) and 57.6 dBc spurious-free dynamic range (SFDR). It is shown that the SINAD is dominated by the signal-to-noise ratio (SNR) of the analog optical link and the SFDR of the proposed system is limited by the linearity of the link.